Analysis of Compensation and Gratitude on Employee Motivation and Performance - Indra Prasetyo, Edwin; Martaleni, Martaleni; Abdul Nasir, M. Jamal (International Journal Labs, 2024)
This study aims to investigate and analyze the impact of several factors on employee performance within the Department of Industry and Trade of Mojokerto Regency, East Java. Specifically, the study examines: 1) the effect of compensation on motivation, 2) the influence of gratitude on motivation, 3) the relationship between compensation and performance, 4) the impact of gratitude on performance, 5) the association between motivation and performance, 6) how compensation affects performance through motivation, and 7) how gratitude influences performance through motivation. The research adopts an explanatory research approach. The population consists of 48 employees with ASN status at the Department of Industry and Trade Mojokerto Regency, all of whom were included in the study using a saturated sampling technique. Data collection involved administering questionnaires directly to respondents. Statistical analysis employed path analysis, preceded by tests for validity, reliability, and assumptions including multicollinearity, heteroscedasticity, and normality. Hypothesis testing utilized a significance level of 5%. The findings indicate that compensation significantly enhances both motivation and performance. Conversely, gratitude does not affect motivation or performance directly. These results underscore the importance of effectively managing compensation strategies to foster employee motivation and enhance organizational performance